Application of Flash Card Media in Learning to Identify Intrinsic Elements of Fantasy Story Text - Tiara Sinto; Herson Kadir; Ayu Hidayanti Ali; Herman Didipu; Eka Sartika (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The problems in this study are (1) how the implementation of flash card media in the learning process of identifying the intrinsic elements of fantasy stories for class VII A students at SMP Negeri 1 Paguyaman Pantai, (2) how student learning outcomes through the application of flash card media in identifying the intrinsic elements of fantasy stories for class VII A students at SMP Negeri 1 Paguyaman Pantai, and (3) what factors influence the application of flash card media in learning to identify the intrinsic elements of fantasy stories for class VII A students at SMP Negeri 1 Paguyaman Pantai. The objectives of this study are (1) to describe the implementation of flash card media in the learning process of identifying the intrinsic elements of fantasy stories for class VII A students at SMP Negeri 1 Paguyaman Pantai, (2) to describe student learning outcomes toward the application of flash card media in learning to identify the intrinsic elements of fantasy stories for class VII A students at SMP Negeri 1 Paguyaman Pantai, and (3) to describe the factors influencing the application of flash card media in learning to identify the intrinsic elements of fantasy stories for class VII A students at SMP Negeri 1 Paguyaman Pantai. The method used in this study is descriptive qualitative. The research data are flash card media. The data sources are the learning activities carried out by teachers and students. Data collection techniques used are observation, interviews, and documentation. Based on the results of the test on identifying the intrinsic elements of fantasy stories conducted on 16 students divided into 3 groups, the average score obtained by students was 93 based on the suitability in identifying the elements of fantasy stories. The conclusion of this study is that the ability to identify the intrinsic elements of fantasy stories of class VII A students at SMP Negeri 1 Paguyaman Pantai meets the assessment standards set by the school.